Pengaruh Lingkungan Kerja Non Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Rejeki Makmur Kediri - Bagus Nur Cahyo W; Iing Sri Hardiningrum; Anita Sumelvia Dewi (Journal of Management and Creative Business, 2023)
Some problems that often occur in the work environment are discomfort with the work environment, this is sometimes caused by a lot of work pressure and mismatches between employees, then the sense of employee discipline that is still considered lacking so that it has a bad impact on company performance activities. This thesis aims to prove the hypothesis of the researcher: there is a partial influence of the Non-Physical Work Environment (X1), work discipline (X2), on employee performance (Y). This study used quantitative methods with multiple linear regression analysis techniques. This research data was obtained by interview, observation, literature study, and questionnaire methods. The sample return in this study used a saturated sampling technique, namely all employees of Rejeki Makmur Kediri as many as 32 people. The results of the study using the help of the SPSS program proposal version 25, showed that: (1) Non-Physical Work Environment partially affected but not significantly on employee performance with a calculated value of -1.423 and a value of Sig. 0.165 > 0.05. (2) and work discipline partially affects employee performance with a calculated value of 3.932 and a value of Sig.0.000 < 0.05 (3) compensation, and work discipline simultaneously has a significant effect on employee performance with a value of Fcalculate 11.043 and a value of Sig. 0.003 < 0.05. From the results of the multiple linear regression analysis test, it produces the equation formula Y = 11.043 + -1.423 X1 + (3.932X2) + e.